Semiotic Analysis of Charles Sanders Pierce in Nuriarta’s Cartoon Discourse - Sani, Komang Andri; Laksana, I Ketut Darma; Simpen, I Wayan (e-Journal of Linguistics; Vol 15 No 2 (2021): enDO - 10.24843/e-jl.2021.v15.i02.p06, 2021)
Nuriarta presents cartoons by utilizing two texts, namely visual text and verbal text. The visual text that is meant is pictures in the form of humans, plants and animals. Verbal text is a series of words that can be read and have meaning according to the message the cartoonist wants to convey. Cartoon discourse by Nuriarta has been uploaded on social media and published in Kompas, Radar Bali, and the Bali Post from 2016 to 2019. Cartoon discourse Nuriarta's work has been published in a book entitled Cartoons and News; Cartoons Bring News and Context by Nuriarta in 2019. The result of research that will be presented is a semiotic analysis of Pierce's nonverbal meaning in cartoon discourse by Nuriarta. The result of research that will be presented is a semiotic analysis of Pierce's nonverbal meaning in cartoon discourse by Nuriarta.